Islamic political parties and elections in Indonesia - Amri, Marwah Fauziah; Bakashmar, Muhammad Rashaad (IIUM Press, International Islamic University Malaysia, 2017)
This study, aims to discover the reason for the decline of PPP's performance in elections. the answers will be sought through a survey of Indonesian worker and students who are voters in Jabodetabek (Jakarta, Bogor, Depok, Tangerang, Bekasi) and from the perspective of PPP itself. In addition the analysis examines the strategies used by the PPP in elections to maintain its political position. Of significant interest to this study is the voting behaviour of Muslim voters who choose candidates based on releigious background.